1996
DOI: 10.1046/j.1469-0705.1996.08030160.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal fetal aortic velocity waveform and intellectual function at 7 years of age

Abstract: Measurements of fetal aortic blood flow velocity and fetal growth were performed in 178 pregnancies. In 87 cases, the estimated fetal weight was > 2 SD below the gestational age-related mean of the population. Three fetuses died in utero. In 148 children (84%) an assessment of overall intellectual ability was performed at 6.5 years of age. Verbal and global IQ was lower in the group with an abnormal fetal aortic blood flow velocity waveform (mean +/- SD 96.0 +/- 17.7 and 95.9 +/- 15.7, respectively; n = 41) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 0 publications
2
41
0
1
Order By: Relevance
“…The blood flow velocity changes are consistent with experimental findings of redistribution of blood flow in IUGR as well as in fetal hypoxia (3,4). We previously showed that abnormal fetal blood flow in fetuses with IUGR is associated with minor neurologic dysfunction and impaired intellectual function at 7 y of age (5,6). The underlying mechanisms whereby IUGR with abnormal fetal blood flow leads to neurologic impairment are largely unknown.…”
supporting
confidence: 86%
“…The blood flow velocity changes are consistent with experimental findings of redistribution of blood flow in IUGR as well as in fetal hypoxia (3,4). We previously showed that abnormal fetal blood flow in fetuses with IUGR is associated with minor neurologic dysfunction and impaired intellectual function at 7 y of age (5,6). The underlying mechanisms whereby IUGR with abnormal fetal blood flow leads to neurologic impairment are largely unknown.…”
supporting
confidence: 86%
“…For patients delivered before that, several observational studies indicate that gestational age is related to motor, social-interactive, habituation and cognitive subscales [62,71,84]. …”
Section: Impact Of Delivery Timingmentioning
confidence: 99%
“…1 Fetuses that are IUGR are more prone to serious complications such as severe fetal distress, cerebral damage, long-term neurological sequelae, and death. [2][3][4][5] A large proportion of small-for-gestational age (SGA) fetuses are IUGR, and the majority of IUGR are also SGA. 1 It has been shown that antepartum identification of SGA, as compared with non-identification and the employment of a surveillance strategy, was related to a four-fold lower risk of severe adverse fetal outcomes.…”
Section: Introductionmentioning
confidence: 99%